The New York Fed DSGE model: A post-Covid assessment - Marco Del Negro; Keshav Dogra; Aidan Gleich; Pranay Gundam; Donggyu Lee; Ramya Nallamotu; Brian Pacula (Federal Reserve Bank of New York, 2024)
We document the real-time forecasting performance for output and inflation of the New York Fed dynamic stochastic general equilibrium (DSGE) model since 2011. We find the DSGE's accuracy to be comparable to that of private forecasters before Covid, but somewhat worse thereafter.
Keywords: E3; E43; E44; C32; C11; C54; 330; DSGE models; real-time forecasts; inflation